Systematic Reviews in Educational Research Methodology, Perspectives and Application - Zawacki-Richter, Olaf; Kerres, Michael; Bedenlier, Svenja; Bond, Melissa; Buntins, Katja (Springer Nature, 2020)
In this open access edited volume, international researchers of the field describe and discuss the systematic review method in its application to research in education. Alongside fundamental methodical considerations, reflections and practice examples are included and provide an introduction and overview on systematic reviews in education research.; Open Access With contributions from international experts First volume with a special focus on systematic reviews in educational research Contains practical examples Takes ethical considerations into account